DArTseq genotyping facilitates the transfer of “exotic” chromatin from a Secale cereale × S. strictum hybrid into wheat - Szőke-Pázsi, Kitti; Kruppa, Klaudia; Tulpová, Zuzana; Kalapos, Balázs; Türkösi, Edina; Gaál, Eszter; Darkó, Éva; Said, Mahmoud; Farkas, András; Kovács, Péter; Ivanizs, László; Doležel, Jaroslav; et al. (Frontiers in Plant Science, 2024)
Cultivated and wild species of genus rye (Secale) are important but underexploited gene sources for increasing the genetic diversity of bread wheat. Gene transfer is possible via bridge genetic materials derived from intergeneric hybrids. During this process, it is essential to precisely identify the rye chromatin in the wheat genetic background. In the present study, backcross generation BC2F8 from a cross between Triticum aestivum (Mv9kr1) and S. cereanum ('Kriszta', a cultivar from the artificial hybrid of S. cereale and S. strictum) were screened using in situ hybridization (GISH and FISH) and analyzed by DArTseq genotyping in order to select potentially agronomically useful genotypes for prebreeding purposes. Of the 329,267 high-quality short sequence reads generated, 27,822 SilicoDArT and 8,842 SNP markers specific to S. cereanum 1R-7R chromosomes were identified. Heatmaps of the marker densities along the 'Lo7' rye reference pseudomolecules revealed subtle differences between the FISH-and DArTseq-based results. This study demonstrates that the 'exotic' rye chromatin of S. cereanum introgressed into wheat can be reliably identified by high-throughput DArTseq genotyping. The Mv9kr1-'Kriszta' addition and translocation lines presented here may serve as valuable prebreeding genetic materials for the development of stress-tolerant or disease-resistant wheat varieties.